Implementation of the development of health protocol guidelines for face-to-face learning in the new adaptation period - Dewi, Tita Kartika; Ambarwati, Tritania (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Covid-19 is a global health problem designated as a pandemic by the World Health Organization (WHO). The covid-19 pandemic has impacted most sectors of life, one of which is the education sector. Educators and education staff are expected to be able to implement a series of face-to-face learning procedures during the new adaptation period in schools Purpose of the research: knowing the effectiveness of the health protocol guidebook on increasing knowledge and attitudes of educators and education staff MI Nagarakasih 2 Tasikmalaya City. Research method: Research using quasy experiment with pretest-posttest group design. Sampling technique with a total sampling of 22 educators and education staff. The instrument uses questionnaires and the development of health protocol guidebooks for face-to-face learning for new adaptation periods in schools. Data analysis using wilxocon test. The results of the research: guidebook of effective health protocols increases the knowledge and attitudes of educators and education staff at MI Nagarakasih 2 School Tasikmalaya City.